The Impact of Preconception TSH on the Reproductive Outcomes of Infertile Women Undergoing the First Fresh D3 Embryo Transfer Cycle - Yuchao Zhang; Wenbin Wu; Yanli Liu; Yichun Guan; Xingling Wang; Liting Jia (International Journal of Endocrinology)
Purpose. To investigate the association between high-normal preconception TSH levels and reproductive outcomes in infertile women undergoing the first fresh D3 embryo transfer. Methods. This was a retrospective study. Euthyroid patients undergoing the first fresh D3 embryo transfer from January 2018 to May 2019 were initially included. The patients were divided into a low-TSH (0.27–2.5 mIU/L) group and a high-normal TSH (2.5–4.2 Miu) group. The reproductive outcomes were compared between the groups. Results. A total of 1786 women were ultimately included, in which 1008 of whom had serum TSH levels between 0.27 and 2.5 mIU/L and 778 of whom had serum TSH levels between 2.5 and 4.2 mIU/L. The patients were highly homogeneous in terms of general characteristics. High-normal TSH levels had no adverse impact on the clinical pregnancy rate, miscarriage rate, or live birth rate (respectively, aOR = 0.92, 1.30, and 0.88 and P = 0.416, 0.163, and 0.219). No significant differences were observed in terms of gestational age, single live birth rates, and birth weight, or birth length. Conclusion. High-normal TSH levels did not significantly influence reproductive outcomes in infertile women undergoing the first fresh D3 embryo transfer. Further studies are needed to test whether the results might be applicable to a wider population.